Attendance management system using face recognition - Jadhav, Ashish; Kamble, Dhwaniket; Rathod, Santosh B.; Kumar, Sumita; Kadam, Pratima; Dalwai, Mohammad (Institute of Advanced Engineering and Science, 2024)
Traditional attendance systems consist of registers marked by teachers, leading to human error and a lot of maintenance. Time consumption is a key point in this system. We wanted to revolutionize the digital tools available in today's time i.e., facial recognition. This project has revolutionized to overcome the problems of the traditional system. Face recognition and marking the present is our project. A database of all students in the class is kept in single folder, and attendance is marked if each student's face matches with one of the stored faces. Otherwise, the face is ignored and not marked for attendance. In our project, face detection (machine learning) is used.